The Effect of Housing Management on Parasite Worm Infection in Gembrong Goats in Two Different Places in Bali Province - Londra, I Made; Sudarma, I Wayan (JURNAL MANAJEMEN AGRIBISNIS; Vol 8 No 2 (2020): OCTOBER 2020DO - 10.24843/JMA.2020.v08.i02.p09, 2020)
The obstacles faced by breeders in maintaining the Gembrong goat in Bali include worm parasites. Gastrointestinal worm infections in goats have an impact in the form of weight loss, anemia, diarrhea, decreased productivity, and economic losses. Research in the villages of Beraban and Abang has been carried out from September to November 2018 with the aim of knowing the effect of housing management on worm infection in gembrong goats in Bali. The study used a fecal sample of 20 gembrong goats aged 7- 15 months, regardless of sex, reared in a staged and postal cage. Samples were checked into BB -Vet Denpasar and tested by the floating concentration method, and egg identification based on morphology. The data obtained were analyzed descriptively. The results of examination of 20 samples found 9 positive samples in stage cages and 13 positive samples in postal cages infected by 22%. After being identified based on egg morphology, it was found in the stage cage pattern of 1,020 grams / faeces, while the postal cage pattern was 1,560 grains of salt / feces. The rate of gastrointestinal worm infections is in the moderate infection stage.